Visualisasi Topologi Jaringan berdasarkan Data Routing Border Gateway Protocol - Rizky Jelang Romadhondaru; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Internet is growing rapidly, communication between internet users is also increasing from time to time around the world. The Internet today is customized by thousands of autonomous systems (AS) that exchange information and communicate using the Border Routing Protocol (BGP) protocol. BGP is a standard gateway routing protocol that is used to introduce to the public outside the network by peering and exchanging network information between US. BGP introduces to other networks with peering to all connected AS and who have been registered in the list of AS numbers. BGP is also responsible for the routing of that occurs between axles and also has an important role in routing. Routing data information can be seen in the RIB or can be called a routing table. Routing information in BGP is so complex and has an extensive network, it is not possible to collect and view routing data one by one. The disadvantage if you look at the data as above is if the BGP has many peers in the US and outside the US in the network. To facilitate the monitoring and evaluation of the BGP Network, a service is needed to monitor and evaluate the network, namely the visualization of BGP routing data. With the aim of saving time, effort and cost in maintaining the BGP network. This final project focuses on the process of how the network topology Border Routing Protocol (BGP) get the service that is by visualization based on data routing Border Routing Protocol (BGP). The network topology is applied to Docker and configured with FRRouting. Visualization is applied to the web interface with Laravel, Tailwind CSS and d3.js. Testing of the visualization system is done by validating the data against the data routing Border Routing Protocol (BGP) with the results of visualization, error testing of the visualization system and testing the best path to the visualization system by changing the route on the routing protocol Border Routing Protocol (BGP). The results obtained visualization system works well in accordance with the function and based on data routing Border Routing Protocol (BGP).